Análisis de las competencias digitales en la formación del profesorado universitario. - Obando Cedeño, Rene Milton (Revista Minerva, 2024)
The information and communication technologies of the twenty-first century are a starting point for the development of digital teaching competences in the educational field, these competences being necessary in higher education. The objective is to review some models of teacher training in order to incorporate a proposal of digital competencies with levels of mastery to better develop university teaching. The study was based on a documentary analysis to compare postulates of various authors on digital teaching competencies to define a training model. In this documentary research it has been found that the greatest obstacle in the training of teachers is not in the knowledge of technical aspects but in the didactic use of technologies. It is also mentioned that it is not only the lack of technological resources or infrastructure that prevents the development of pedagogical practice, but also the socio-educational, motivational and curricular contexts immersed in the educational task. The knowledge gathered in this article reveals that digital competencies with a critical, ethical and reflective use are a viable alternative for the development of skills and abilities in teachers in order to strengthen the fquality of education in higher education.